Social Media: A Neo Form of Learning Platform - Neupane, Nirmal (Janabhawana Research Journal, 2023)
“Can social media be considered a neo-form of learning platform for students in this globalized digital world?" Social media is not only used for communication and entertainment purposes but is also highly popular among students for collaboration and learning purposes. This paper aims to explore how social media has evolved into a neo-form of learning platform, enabling students to acquire diverse knowledge to enhance their academic and professional careers. The primary source for this exploration is a review of existing literature, supplemented by personal experiences and relevant examples to support the claim. The discussion on why social media serves as a beneficial learning platform revolves around four major themes: its student-centric learning approach, its ability to enhance personal learning environments, its promotion of flexible and inclusive learning, and its role as a milestone for information and communication in academics and professional careers. In conclusion, the analysis confirms that social media is indeed becoming an effective neo-learning platform for students.